Coil-like Enzymatic Biohybrid Structures Fabricated by Rational Design: Controlling Size and Enzyme Activity over Sequential Nanoparticle Bioconjugation and Filtration Steps - Ennen, Franka; Fenner, Philipp; Stoychev, Georgi; Boye, Susanne; Lederer, Albena; Voit, Brigitte; Appelhans, Dietmar (ACS Applied Materials and Interfaces, 2016)
Well-defined enzymatic biohybrid structures (BHS) composed of avidin, biotinylated poly(propyleneimine) glycodendrimers, and biotinylated horseradish peroxidase were fabricated by a sequential polyassociation reaction to adopt directed enzyme prodrug therapy to protein-glycopolymer BHS for potential biomedical applications. To tailor and gain fundamental insight into pivotal properties such as size and molar mass of these BHS, the dependence on the fabrication sequence was probed and thoroughly investigated by several complementary methods (e.g., UV/vis, DLS, cryoTEM, AF4-LS). Subsequent purification by hollow fiber filtration allowed us to obtain highly pure and well-defined BHS. Overall, by rational design and control of preparation parameters, e.g., fabrication sequence, ligand-receptor stoichiometry, and degree of biotinylation, well-defined BHS with stable and even strongly enhanced enzymatic activities can be achieved. Open coil-like structures of BHS with few branches are available by the sequential bioconjugation approach between synthetic and biological macromolecules possessing similar size dimensions.
CRIS-Team Scopus Importer:2023-03-20
Keywords: avidin-biotin; coil-like structure; enzyme; glycodendrimer; sequential bioconjugation